GE_GERICHTE A/2693/2023 vom 17. Oktober 2016 - GE Cour de justice (2016)
MESURE DE CONTRAINTE(DROIT DES ÉTRANGERS);DÉTENTION AUX FINS D'EXPULSION | LEI.76.al1.letb.ch1; LEI.76.al1.letb.ch3; LEI.76.al1.letb.ch4; LEI.75.al1.leth